Adaptation to online teaching of field practices in coastal engineering courses - Pagán Conesa, José Ignacio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Field practices are ideal for the acquisition of specific competencies and for students to get a first-hand experience of the real environment of their profession. The COVID19 pandemic stopped them, forcing a move to online teaching. This research aims to define a new teaching approach to adapt them to the online environment, ensuring that the competencies are acquired in the same way as traditionally. It was decided to use various available audio-visual materials (documentaries, video reports, interactive web resources) from different sources. The results obtained were very positive, as the advantages provided by ICT resources outweigh the disadvantages.